Theoretical Research of the Machining of the Few Tooth Number Gear with the Y38 Hobbing Machine - Wang Baomin; Guo Hongfeng; Chen Changbiao; Ma Yuelin; Chai Xiaoyu (Jixie chuandong)
According to the principle of generation method and the case of Y38 hobbing machine spare wheels,the feasibility of the machining of few tooth gear with tooth number less than eight by using Y38 hobbing machine is theoretically analyzed. On the basis of the experiment,the reason why the hobbing machine can ’t start normally when machining the few teeth number gear is analyzed,and the renovation scheme is put forward.After transforming,the few tooth number gear can be machined by using the Y38 hobbing machine.